Phenotypic and Genotypic Analysis of Amino Acid Auxotrophy in Lactobacillus helveticus CNRZ 32 - Christiansen, Jason K. (American Society for Microbiology (ASM), 2008)
The conversion of amino acids into volatile and nonvolatile compounds by lactic acid bacteria in cheese is thought to represent the rate-limiting step in the development of mature flavor and aroma. Because amino acid breakdown by microbes often entails the reversible action of enzymes involved in biosynthetic pathways, our group investigated the genetics of amino acid biosynthesis in Lactobacillus helveticus CNRZ 32, a commercial cheese flavor adjunct that reduces bitterness and intensifies flavor notes. Most lactic acid bacteria are auxotrophic for several amino acids, and L. helveticus CNRZ 32 requires 14 amino acids. The reconstruction of amino acid biosynthetic pathways from a draft-quality genome sequence for L. helveticus CNRZ 32 revealed that amino acid auxotrophy in this species was due primarily to gene absence rather than point mutations, insertions, or small deletions, with good agreement between gene content and phenotypic amino acid requirements. One exception involved the phenotypic requirement for Asp (or Asn), which genome predictions suggested could be alleviated by citrate catabolism. This prediction was confirmed by the growth of L. helveticus CNRZ 32 after the addition of citrate to a chemically defined medium that lacked Asp and Asn. Genome analysis also predicted that L. helveticus CNRZ 32 possessed ornithine decarboxylase activity and would therefore catalyze the conversion of ornithine to putrescine, a volatile biogenic amine. However, experiments to confirm ornithine decarboxylase activity in L. helveticus CNRZ 32 by the use of several methods were unsuccessful, which indicated that this bacterium likely does not contribute to putrescine production in cheese.